Perlite concrete. 1. Density and compressive strength in relation to mix proportions and methods of curing - Blakey, F. A. (Frank A.) (Report C (CSIRO. Division of Building Research) ;, 1958)
The effect of four different curing treatments on the compressive strength,and de1lsity of perlite concretes of different mix proportions is studied. The results show that the strength and density of the concrete decreases with increasing perlite content and with the use of air entrain- ment. Unexpectedly low strengths were obtained with concrete cured in high pressure steam, and possible explanations for this behaviour are noted.